Stimulating Self-Regulation: A Review of Non-invasive Brain Stimulation Studies of Goal-Directed Behavior - Kelley, Nicholas J.; Gallucci, Alessia; Riva, Paolo; Romero Lauro, Leonor Josefina; Schmeichel, Brandon J. (Frontiers in Behavioral Neuroscience, 2019)
Self-regulation enables individuals to guide their thoughts, feelings, and behaviors in a purposeful manner. Self-regulation is thus crucial for goal-directed behavior and contributes to many consequential outcomes in life including physical health, psychological well-being, ethical decision making, and strong interpersonal relationships. Neuroscientific research has revealed that the prefrontal cortex plays a central role in self-regulation, specifically by exerting top-down control over subcortical regions involved in reward (e.g., ventral striatum) and emotion (e.g., amygdala). Here we review experiments using non-invasive brain stimulation techniques (e.g., transcranial direct current stimulation, transcranial magnetic stimulation) to target prefrontal brain regions implicated in self-regulation. We focus on brain stimulation studies of self-regulatory behavior across three broad domains of response: persistence, delay behavior, and impulse control. We suggest that stimulating the prefrontal cortex may promote successful self-regulation by altering the balance in activity between the prefrontal cortex and subcortical regions involved in emotion and reward processing.